Improving The Students’ Writing Skills of Class VIII-A at SMPN 2 Panji by using Picture Series - Dwi Sukwantoro (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Writing is defined as a productive skill which helps the students to express their ideas and opinions in readable writing. Therefore, by learning to write, they are able to communicate effectively through good writing. Having good writing skill will help students in applying for jobs, important papers, and academic concerns; it also can be used in writing written and academic works. This research was intended to review the role of picture series as one of the learning media in improving students' writing skills. To achieve this objective, theory presentation, regulation, research, and practice in teaching writing were done. The students of III-A at SMPN 2 Panji were taken as research subjects. The research approach used was a qualitative research approach as the data obtained from the results of observation, interview, and students’ learning outcomes; and emphasized the process rather than focused on learning outcomes. This research was classified as a classroom action research by using two cycles in four stages; planning, implementing, observing, and reflecting. Each cycle was conducted in two meetings. Based on the results of the research, students’ learning outcomes improved from only 45% students in class VIII-A who were able to pass KKM in pre-cycle to 80% students who reached KKM in the cycle II. The students’ mean scores increased from 63 to 80 at the end of the second cycle. Thus, the conclusion drawn is learning to write by using picture series improved the students’ learning outcomes in class VIII-A at SMPN 2 Panji.